Undergraduate student research experiences: a call for ICT-aided supervision - Chauraya, Effiritha; Moyo, Annah (International Journal of Research and Innovation in Social Science, 2019)
This paper makes an analysis of undergraduate students’ experiences of their research supervision at a state university in Zimbabwe. Undergraduate students’ research supervision experiences during their studies varied, mostly dichotomously. While some students experienced rewarding and gratifying experiences, others, however, underwent frustration, constringent and stressful experiences. Faculties did not show any significant variations, but mode of entry did. Most visiting/block students recorded more negative than positive experiences about their supervisory process. The study concludes with suggestions to reduce student vulnerability and enhancement of the quality of the supervision process. Key suggestions included that: faculties set up research project monitoring focal persons, supervisors be trained in research supervision, and also that both supervisors and students be trained in ICT.